Le mémoire en formation infirmière en France : exemple d’un dispositif à visée socioconstructiviste - Marielle Boissart (Recherches en Éducation)
In France, bringing the training of nurses to a university level has made Nursing Research a major issue, within the development of that vocational experience. Developing the required skills to address the population’s health needs represents a true challenge. So as to answer to this dual movement towards university training and professionalization, educational thoughts rank first in the building up of the training schemes. In this article, we are proposing an research experiment within our institution which focuses on a socio-constructivist approach. This way, the students are putting forward an individual training presentation, related to their Master’s Thesis in front of their peers, and a jury composed of executive health trainers. At the starting point of an aprioristic research methodology, the spheres of psychology, sociology and anthropology highlight the impact of an interactive educational approach on the professionalization process of the student, during the preparation of the Master of Research. The results emphasize the fact that the memorandum plays its part in the student’s professionalization thanks to the conceptualization it induces, and the reflexiveness ability related to it. However, those results clearly emphasize too, that knowledge can’t possibly be acquired within social interaction alone. Actually, the role of an executive health trainer is that of a mediator and a regulator of the students’ learning processes, so as to turn the interpersonal processes into intrapersonal ones.